[Aetas ; Philippine Eagle ; Mamang sorbetero [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1992)
Visit to the Aeta resettlement area in Buhawon Zambales. Interview with Aeta children about their experiences during the Pinatubo eruption; tells us why the Philippine eagle is now an endangered species; visit of a local ice cream maker to see how "dirty ice cream" is made.
Aetas (12 min.) -- Philippine Eagle (14 min.) -- Mamang sorbetero (11 min.)
VHS.
Keywords: Ayala, Joey -- Interviews; Negritoes -- Social conditions; Negritoes -- Economic conditions; Ice cream, ices, etc; Ice cream parlors -- Philippines